Case Report: A case of interstitial pneumonia in a colorectal cancer patient with a history of lung cancer treated with cetuximab - Yang, Yang; Zhang, Bin; Li, Hongjun; Ren, Mei; Chong, Daoqun; Guo, Yujin; Zhao, Haibo; Yu, Qing-Qing (Frontiers in Oncology, 2025)
PurposeThis study aims to investigate the pathogenesis, clinical manifestations, and prognosis of interstitial lung disease (ILD) induced by cetuximab.Patients and methodsA single case of a colorectal cancer patient who underwent radical resection and descending colon-rectal anastomosis for sigmoid colon cancer on October 22, 2020, was selected. Postoperative pathology revealed moderately differentiated adenocarcinoma confined to the mucosa, measuring approximately 0.5×0.2×0.2 cm, with no cancer involvement in the proximal and distal resection margins, and metastatic carcinoma observed in 1 out of 5 pericolic lymph nodes. On July 29, 2021, due to a significant increase in CA19–9 levels, chest and abdominal CT scans, along with brain MRI, indicated enlarged retroperitoneal lymph nodes. The patient was afebrile and without respiratory symptoms such as cough, sputum production, chest tightness, or shortness of breath, and imaging suggested disease progression. With no significant abnormalities in C-reactive protein, blood routine, and no evidence of infection, cetuximab-related ILD was considered. Due to mild inflammation, the patient continued cetuximab combined with chemotherapy.ResultsThis study suggests that cetuximab can induce ILD, and the onset time may be associated with factors such as serum albumin levels and underlying pulmonary diseases.ConclusionThe incidence of cetuximab-induced ILD is low and relatively rare, with non-specific clinical symptoms. Clinically, treatment plans should be tailored to the patient’s actual condition to control disease progression and improve patient prognosis.